Does work influence women’s autonomy or does autonomy deliberate women to work? - Ristiana Ruskin; Handayani Dwini (E3S Web of Conferences, 2018)
Work, especially paid work, has been assumed to enhance women’s autonomy, particularly their household autonomy. However, this assumption does not work in one causal direction. The causality relationship works both ways, that women work due to their high level of autonomy, but also because their employment status will increase their autonomy. The aim of this study is to understand the relationship between women’s work status and their household autonomy. This study used data from the Indonesian Demography and Health Survey 2012, together with a multinomial logistic regression analysis on married women’s work status and autonomy as dependent and independent variables, respectively. It was found that work status influences married women’s household autonomy and vice versa. However, the direction and strength of the influence depend on the type of work status and autonomy.